Seguimiento a recomendaciones de la Estrategia Nacional de Inmunizaciones para menores de 1 año. Riobamba, 2019-2020 - Soria Freire, Andrés Gabriel (2021)
Vaccination for a long time in Ecuador has been a primary entity for the socioeconomic, cognitive, cultural and institutional development of a human being; This process begins at birth and extends through adolescence. The Ministry of Public Health through the National Immunization Strategy aims at effective health intervention to help reduce infant morbidity and mortality General Objective: Evaluate the prevalence of users of national vaccination program through monitoring of the population of children under one year of age and also the use of the survey technique to corroborate the factors that cause the in the Canton Riobamba,2019 -2020. Material and Methods: A descriptive, non-experimental and cross-sectional study was carried out, in which 50 surveys of caregivers who attend Health Center No. 1 with children under one year were analyzed, in addition to the study of the population of the years 2019 and 2020 through the use of the quantitative-qualitative method and the use of information cakes. Results: Of the 50 surveys carried out at random to caregivers who attended the Health Center N ° 1 with children under 1 year of age, it was determined that the female population is greater than the male, surpassing this with 38%, both the mother and the father turned out to be the people who frequently accompany the children, obtaining a higher percentage, and 76% of them possess the card for their follow-up; Through the surveys we also check the degree of knowledge, one of these is that of the vaccination itself, of which 96% consider this practice necessary; Regarding the knowledge of diseases, 72% were able to respond and in the same way regarding the reactions that it produces, an unfavorable result was obtained with 76% Conclusion: It was determined that not all vaccines meet the goals established by the Ministry of Public Health towards Health Center No. 1, such is the case of Hb, which requires further analysis to prevent chronic diseases.